Manajemen Kompensasi dalam Meningkatkan Profesionalisme dan Kinerja Guru di Lembaga Pendidikan - Aradatullah Dita Illahiyah; Frida Magdalena; Syahla Athia Farha (Program Studi Magister Manajemen Pendidikan, 2025)
Compensation management is one of the strategic aspects of human resource management in education. Compensation is not only understood as financial remuneration, but also as an instrument to improve teachers’ motivation, professionalism, welfare, and performance. This article aims to describe the basic principles of compensation management, its management mechanisms, the impacts of compensation implementation, and the challenges of its application in educational institutions. This study employed a literature review method with a qualitative descriptive approach through the analysis of books, journals, and previous studies related to educational compensation management. The findings indicate that a fair, transparent, and performance-based compensation system can improve work motivation, loyalty, job satisfaction, and the quality of learning. Previous studies also show that effective compensation positively influences teacher professionalism and educational quality. However, the implementation of compensation management still faces several challenges, such as budget limitations, inequity in reward systems, regulatory changes, and the evolving needs of the modern workforce. Therefore, compensation management should emphasize fairness, transparency, sustainability, and technological support to enhance the effectiveness of educational human resource management.